Alginates - Recent Uses of This Natural Polymer 2020
DOI: 10.5772/intechopen.90426
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Alginate Bioink for 3D Bioprinting in Tissue Engineering and Regenerative Medicine

Abstract: Among many bioinks used for extrusion 3D bioprinting, the most commonly used bioink is the polysaccharide alginate because of its various cellular-friendly property like gelation. Erratic degradation and cell-binding motifs are not present in alginate which are the limitations of alginate bioinks, which can be improved by blending various low concentrations of natural or artificial polymers. Here in this chapter, we will discuss the various important properties of the alginate which make it as the bioink for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 50 publications
(59 reference statements)
0
18
0
Order By: Relevance
“…Previous studies have shown that eggwhite is a biocompatible, non-toxic biomaterial [14] and that alginate is a commonly used biomaterial in cell printing [44]. Our present study examined the HUVEC viability in the EW-2%Alg printed construct post-bioprinting, which could be affected by the mechanical forces that the cells experienced during the bioprinting process.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown that eggwhite is a biocompatible, non-toxic biomaterial [14] and that alginate is a commonly used biomaterial in cell printing [44]. Our present study examined the HUVEC viability in the EW-2%Alg printed construct post-bioprinting, which could be affected by the mechanical forces that the cells experienced during the bioprinting process.…”
Section: Discussionmentioning
confidence: 98%
“…The authors of a previous study observed a significant improvement of the healing process and monocyte stimulation, as well as higher cytokine levels, such as tumor necrosis factor-α and interleukin-6 [ 128 ]. It was also proven that alginate might be useful in reconstructive surgery and bone regeneration, e.g., alginate scaffolds helped in bone tissue formation [ 129 ].…”
Section: Materials Additives Used In Gel Systemsmentioning
confidence: 99%
“…The very porous and surface scaffolds were used to distribute bioactive glass homogenously. The presence on the surface of composite 7 International Journal of Polymer Science scaffolds of calcium phosphate deposits in vitro bioactivity [95]. The metabolism of fibroblast was boosted by bioactive glass.…”
Section: Synthetic Biopolymer-based Compositesmentioning
confidence: 99%